Memantik Pengaruh Desain dan Kualitas Produk terhadap Keputusan Pembelian - Fajariah, Faizatul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The study aims to analyze the influence of product design and quality on purchasing decisions at PT. JMA Furniture Klaten, Central Java. The research method used in this study uses a quantitative method. The population of employees working at CV SAI Semarang is 96 people. This study uses a non-probability sampling approach method with a saturated sampling technique. The data analysis technique used is the classical assumption test, determination coefficient test, hypothesis test processed using IBM SPSS software version 26. The research instrument uses a questionnaire and interview list. The results of the study showed that design partially has a positive and significant effect on purchasing decisions at PT. JMA Furniture Klaten, Central Java, while product quality partially has a positive and significant effect on purchasing decisions at PT. JMA Furniture Klaten, Central Java. Simultaneously, design and product quality have a positive and significant effect on purchasing decisions at PT. JMA Furniture Klaten, Central Java.